Substitution of arabica coffee powder to enhance antioxidant content in traditional Bhoi cake for Gen-Z - Nazarrahmah Nazarrahmah; Nani Ratnaningsih; Badraningsih Lastariwati; Putri Rahmah Nur Hakim; Lina Marlina (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
This study aimed to develop a functional food innovation by incorporating Arabica coffee into traditional Bhoi cakes to address the demand for healthier dietary options among Generation Z. This study applied a Research and Development (R&D) approach using a 4D model (define, design, develop, and disseminate). The study was conducted from January to May 2025 at the Food Technology and Nutritional Chemistry Laboratory of Banda Aceh. Ten experts and 80 untrained panelists were recruited through purposive sampling. Arabica coffee powder was substituted at 5%, 7.5%, and 10% of the flour weight. The proximate composition, antioxidant activity (UV-Vis spectrophotometry), and sensory attributes of the samples were analyzed. Statistical analyses were performed using paired t-tests at a 5% significance level. The results showed that 10% substitution significantly increased the antioxidant activity (34.7 ± 1.2 mg GAE/g) compared to that in the control (18.5 ± 0.9 mg GAE/g, p < 0.01). Sensory evaluation also indicated higher preference scores for color, aroma, taste, and texture at the 10% level (p < 0.05). In conclusion, the Arabica coffee-based Bhoi cake demonstrates the feasibility of enriching traditional foods with functional properties while preserving their cultural identity. This innovation may serve as a model for developing functional foods based on local culinary heritage.